IMPROVING THE QUALITY OF ISLAMIC EDUCATION THROUGH THE ROLE OF STUDENTS - Prasetyo, Teguh (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
Education is a conscious effort made by individuals and institutions through teaching, coaching, and training for developing human potential in the face of challenges in the future. Students as agents of change to take an important role in society. One of the implementation of the active role of students and professors University Djuanda Bogor implement Kuliah Kerja Nyata (KKN) started in August 2016 for an independent and integrated with the findings in the field. The location is in the implementation of Village Buntar, South Bogor. The result of this dedication also involve faculty and students. One of the changes is the concern of the people of Village Buntar to improve the quality of education, especially through Islamic elementary schools and early childhood. The efforts or programs that have been implemented include; (1) teaching in educational institutions madrasah and early childhood, (2) Tutoring, (3) training of learning tools, (syllabus and lesson plans), (4) Socialisation of madrasah islamic education, and (5) seminar to be a professional teacher. Recommendations by the dedication of the students can give recommendations to citizens, teenagers, structural villages, and the city government can work synergistically to promote education in Village Buntar.